The Meaning of Keris Jawa and Effort For Their Preservation in a Sociological Perspektive : Study of The Tosan Aji Panji Patria Association - Novi Catur Muspita; Fandi Sudiasmo; Fandu Dyangga Pradeta (Universitas Islam Balitar, 2021)
Keris is a cultural product that holds a million mysteries to be guarded and preserved, keris has been recognized by UNESCO, every Friday Legi the Blitar community gathers there is a keris exhibition at (PIPP) Blitar. The aims of this study are: (1) to identify and analyze the meaning of Keris Jawa in a sociological perspektive, (2) to identify and analyze conservation efforts it, (3) to identify and analyze the supporting and inhibiting factors in the conservation of it: a study of the Tosan Aji Panji Patria community. The research method uses qualitative research. The results of the study: (1) The meaning of Keris Jawa ; (a) Keris as accessories for ceremonial clothing during cultural ritual ceremonies, (b) Keris as a souvenir, (c) Keris has meaning high philosophy, namely about faith in God and procedures for holding, opening, and inserting a keris, (e) learning about metal, copper, steel and meteors as well as iron science, (2) Efforts to preserve Keris Jawa: (a) routine activities every Friday Legi, namely the keris exhibition, (b) socialization of keris as artistic and cultural value at discussion events (c) the joint commitment of the government and the community to preserve it, (3) Supporting factors in the effort to preserve Keris Jawa: ( a) The Blitar Government supports and facilitates Keris exhibition at PPIP, (b) the enthusiasm of the community is very high at every Keris exhibition event, while Covid-19 pandemic, activities in limit.